Analysis of the electrically driven gas pumping units application advantages - Иванов, Вадим Борисович (Technology audit and production reserves, 2016)
This article discusses the impact of operational, environmental and economic factors on the drive choice to equip the gas pumping units. The main aim of this study is to analyze the factors influencing the choice of drive type, show the advantages of EDGPU, to determine the necessary conditions for their application. Comparison of frequency-controlled, hydrodynamic and mechatronic electric driven units with turbine driven is done based on the indicators of availability and the ability to implement different load regimes, efficiency, technological readiness and service life of equipment, ease of placement and need for production areas, requirements to energy supply and quality of gas quality, impact on the environment. Analysis on the basis of economic criteria includes consideration of the required investment costs, operating costs, including the costs of maintenance and repairs, the life cycle cost. Research results can be used for design of new and modernization of existing compressor stations of main gas pipelines, as well as the choice of technological compressors in various industries.